Correlation Between Retinal Microstructure Detected by Optical Coherence Tomography and Best Corrected Visual Acuity in Diabetic Retinopathy Macular Edema - Li, Siying; Hua, Rui; Jing, Zuoqian; Huang, Lele; Chen, Lei (Frontiers in Endocrinology, 2022)
Objective: This study aimed to investigate the correlation between best corrected visual acuity (BCVA) and retinal microstructural parameters detected by optical coherence tomography (OCT) in diabetic retinopathy macular edema (DRME). Methods: Thirty-nine patients (64 eyes) with DRME were enrolled in this study. These patients underwent OCT to measure the fracture distance of the external limiting membrane (ELM), junction between the inner and outer segments (IS/OS), central foveal thickness (CFT), and edema layer. The correlation between the above parameters and BCVA was discussed. Results: CFT and the fracture distances of the ELM and IS/OS layers were negatively correlated with BCVA (p<0.05 for all).There was significant difference in Logarithm of the minimum angle of resolution (LogMAR) BCVA among patients with inner retinal edema, outer retinal edema, and mixed retinal edema (F = 5.57, p = 0.01). The LogMAR BCVA of inner retinal edema was the lowest (p < 0.05), and the LogMAR BCVA of outer retinal edema and mixed retinal edema were comparable (p > 0.05). Conclusion: In eyes with DRME, thin CFT, intact ELM and IS/OS layers, and edema in inner retina is closely correlated with good BCVA.